How to protect entitlements: An experiment - Oren Bar-Gill; Christoph Engel (Max Planck Institute for Research on Collective Goods, 2017)
In a full-information, zero transactions costs world, the degree of protection afforded to an entitlement does not affect the likelihood of efficient trade. In reality, imperfect information is often inevitable. Specifically, a party will usually have incomplete information about fairness norms held by the other party - fairness norms that affect the other party's willingness to pay (WTP) or willingness to accept (WTA). Importantly, these fairness norms may depend on how strongly the entitlement is protected. We experimentally test the effect of the degree of protection on the parties' WTP and WTA and on the likelihood of efficient trade by varying the legal remedy for infringing upon the owner's entitlement. We show that our participants can be divided into three groups corresponding to three different fairness norms: negative types whose WTP and WTA are decreasing in the strength of the legal remedy; positive types whose WTP and WTA are increasing in the strength of the legal remedy; and flat types whose WTP and WTA do not depend on the strength of the legal remedy. We find that type is role-dependent, such that a higher WTP and a lower WTA - the combination most conducive to efficient trade - is obtained with a weaker legal remedy.
Keywords: C78; C91; D12; D63; K11; K12; 330; property rule; liability rule; damages; compensation; coase theorem; bargaining; fairness; equality; desert; entitlement; taking